Association between Oral Pathology, Carotid Stenosis, and Oral Bacterial DNA in Cerebral Thrombi of Patients with Stroke. (7th September 2021) - Patrakka, Olli; Mehtonen, Helena; Tuomisto, Sari; Pienimäki, Juha-Pekka; Ollikainen, Jyrki; Huhtala, Heini; Pessi, Tanja; Oksala, Niku; Lehtimäki, Terho; Järnstedt, Jorma; Martiskainen, Mika; Karhunen, Pekka J.
Abstract : Background and purpose . Risk of acute ischemic stroke has been associated with carotid artery atherosclerosis as well as with periodontal disease. We studied whether oral pathology or carotid atherosclerosis was associated with the presence and quantity of bacterial DNA in their aspirated thrombi. Methods . Thrombus aspirates and control arterial blood were taken from 71 patients (70.4% male; mean age, 67.4 years) with acute ischemic stroke. Tooth pathology was registered using CT scans. Carotid stenosis was estimated with CTA and ultrasonography. The presence of bacterial DNA from aspirated thrombi was determined using quantitative PCR. We also analyzed the presence of these bacterial DNAs in carotid endarterectomies from patients with peripheral arterial disease. Results . Bacterial DNA was found in 59 (83.1%) of the thrombus aspirates (median, 8.6-fold). Oral streptococcal DNA was found in 56 (78.9%) of the thrombus aspirates (median, 5.1-fold). DNA from A. actinomycetemcomitans and P. gingivalis was not found. Most patients suffered from poor oral health and had in median 19.0 teeth left. Paradoxically, patients with better oral health had more oral streptococcal DNA in their thrombus than the group with the worst pathology (p = 0.028 ). There was a trend (OR 7.122; p = 0.083 ) in the association of ≥50% carotid artery stenosis with more severe dental pathology. Oral streptococcal DNA was detected in 2/6 of carotid endarterectomies. Conclusions . Stroke patients had poor oral health which tended to associate with their carotid artery stenosis. Although oral streptococcal DNA was found in thrombus aspirates and carotid endarterectomy samples, the amount of oral streptococcal DNA in thrombus aspirates was the lowest among those with the most severe oral pathology. These results suggest that the association between poor oral health and acute ischemic stroke is linked to carotid artery atherosclerosis.